CT-scan findings of COVID-19 pneumonia based on the time elapsed from the beginning of symptoms to the CT imaging evaluation: a descriptive study in Iran - Jafari Sirous; Tabary Mohammadreza; Eshraghi Sahereh; Araghi Farnaz; Aryannejad Armin; Mohammadnejad Esmaeil; Rasoolinejad Mehrnaz; Hajiabdolbaghi Mahboubeh; Koochak Hamid Emadi; Ahmadinejad Zahra; Abbasian Ladan; Manshadi Seyed Ali Dehghan; et al. (Sciendo, 2020)
Background. Coronavirus disease 2019 (COVID-19) was initially detected in Wuhan city, China. Chest CT features of COVID-19 pneumonia have been investigated mostly in China, and there is very little information available on the radiological findings occurring in other populations. In this study, we aimed to describe the characteristics of chest CT findings in confirmed cases of COVID-19 pneumonia in an Iranian population, based on a time classification.